Use the quadratic formula to find the real solutions of the equation 2x^2-3x=1
5 answers
I really need help with this one because I was absent for this portion of the notes because I got called down to guidance can someone please help me and explain this to me
2 x^2 - 3 x - 1 = 0
x = [ 3 +/- sqrt (9+8) ] / 4
= [ 3 +/- sqrt(17) ] / 4
x = [ 3 +/- sqrt (9+8) ] / 4
= [ 3 +/- sqrt(17) ] / 4
well
if a x^2 + b x + c = 0
then
x = [ -b +/- sqrt(b^2-4ac) ] / 2a
if a x^2 + b x + c = 0
then
x = [ -b +/- sqrt(b^2-4ac) ] / 2a
Thank you so very much Damon.
You are welcome.